(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The discharge of wastewater containing suspended solids into an open water body has a very negative impact on the condition of the water. The suspended solids sink to the bottom of the water, turbidizing the water, or slowing down or completely stopping the vital activity of bottom microorganisms involved in the process of self-purification of water. As a result of the decomposition of bottom sediments, harmful and even toxic substances, such as hydrogen sulfide, can be formed, which subsequently renders the river water completely unusable.